Response of sunflower (Helianthus annuus L.) based cropping systems to fertilizer levels: Response of sunflower (Helianthus annuus L.) based cropping systems to fertilizer levels - D SWETHA,; A V RAMANJANEYULU,; D SRAVANTHI,; N SAINATH, (Journal of Oilseeds Research, 2020)
Field experiment was conducted during 2018-19 to study the effect of different preceeding crops and fertilizer levels on yield and economics of rabi sunflower. Significantly higher sunflower equivalent yield was obtained in maize-sunflower cropping system (2071 kg/ha) which is on par with greengram-sunflower cropping system (2060 kg/ha). Application of 100% RDF recorded significantly higher sunflower equivalent yield (1785 kg/ha) than 50% STCR (1428 kg/ha) but on par with that of 100% STCR (1650 kg/ha). The highest system gross returns, net returns and B: C ratio were obtained with greengram-sunflower and 100% RDF fertilizer.